Public Leadership: Perspectives and practices - `t Hart, Paul (ANU Press, 2008)
'Leadership' is routinely admired, vilified, ridiculed, invoked, trivialised, explained and speculated about in the media and in everyday conversation. Despite all this talk, there is surprisingly little consensus about how to answer basic questions about the nature, place, role and impact of leadership in contemporary society. This book brings together academics from a broad array of social science disciplines who are interested in contemporary understandings of leadership in the public domain. Their work on political, administrative and civil society leadership represents a stock-take of what we need to know and offers original examples of what we do know about public leadership. Although this volume connects scholars living in, and mostly working on, public leadership in Australia and New Zealand, their contributions have a much broader scope and relevance.